Executive Development Programs - Jucius, Michael J.; Folts, Franklin; Simpson, Hoke; Johnson, Howard; Donham, Richard S.; Goetz, Billy E. (Academy of Management Journal, 1958)
Reports on an annual executive development program held in Philadelphia, Pennsylvania on December 28, 1957 by the Academy of Management. Kinds of management.